Basketball feint and non-verbal communication: empirical framework - Raiola, G. (Journal of Human Sport & Exercise, 2015)
Bodily communication has its own epistemological framework in which the message follows a process of encoding, transmission and decoding. It establishes contacts and relationships that are developed first by data processing and after by message content evaluating. It has, within it, an ethnic-social substrate that changes in different cultures and contexts. It is a dynamic flow consisting of five basic elements: context, sender, recipient, channel, code and follows a logical and analogical process. The arguments of bodily communication affect the feint, which means manifest intention of achieving a goal through the initial implementation of a plan with specific motor signs, postures, attitudes, which are later implemented in totally different pursuance It refers to the "tactics" decoding of bodily communication. In this way, non verbal communication have to be included both in experimental and human sciences, so it can investigated by observation and data collected and get together the quantitative and qualitative aspects. The game situations in basketball are so many variables, determined from interacting behaviors engines all players, between teammates and against the opponents. The behaviors of the feints are of great importance both that quality execution technique that every player has and to choice the tactical option. In this study, it is request to recognize the main aspects in basketball, such as in volleyball in past study and to give an argumentative and deductive classification. Method is the observation by descriptive research of three experts: coach of team, experts of body communication and performance analyst. Results show some interested aspects. The body feint is always a deliberate attempt to deceive the opponent to gain an advantage in the context of the game, moreover, it is the basis of the game of basketball, along one players against one, on which is built the complex process of acquisition of tactical advantages over opponents. There are some prerequisites to be able to realize the motor actions of fake, definitely a good knowledge of the rules of the game, knowing how to hesitate (take time before changing direction) or anticipate a move (make a cut changing speed) and especially the ability to read situations game tactics. In conclusion, for young athletes, the education of these aspects becomes essential to ensure the development of the imagination and anticipation motor, which imply the ability of invention and adaptation to different situations of the game. The more a player forces the opponent to react to his feint (shooting, passing or departure dribble), instead of acting, the more likely will have to gain the benefits (time and space) in order to carry out his plan motor effectively (to make an easy score). Although, it is to highlight that, in the modern basketball defensive tactics (zone press, help and recovery, doublings, defensive switch, etc.) start to work out the following game situations: the defender must not have more behavior liabilities compared to the attacker, but in turn must perform the behavior of pretending to try to reverse the situation tactic, creating disorientation, or otherwise, creating an unexpected situation for the attacker; in order to create; an advantage for the defense (recovery of the ball on the dribble, on the steps or on the shoot).